Relación de las estrategias digitales en las ventas de la empresa CASPIANA de Lima Metropolitana en el periodo 2019 - Chávez Campoverde, Naomi Alessandra (2021)
E-commerce has been growing over the years and little by little companies are starting to go digital to be more competitive. The problem resides when there is no prior planning or the appropriate strategies are not identified according to the channel or public, generating a loss of money or customers. It is especially important to know which digital strategies are of greater impact for the public. With this information, efforts can be focused on developing digital strategies that generate more value and impact on sales, and a good strategy draws attention and allows for building ties with the customer. In addition, this research will provide a broader picture within the digital marketing arm and will provide more insight into the value people place on specific digital marketing strategies in content marketing, video marketing, and mobile marketing.